Career services at HEI’s: what are they offering? - Khurumova, Veronika; Pinto, Joana Carneiro (Frontiers in Education, 2024)
Higher education career centers should tailor their services toward empowering students to make them employable after graduation to meet the demands of the 21st century world of work. This paper aims to reflect on career counseling services provided by Higher Education Institutions. We start by presenting a brief history of their development around the world, with particular emphasis on Portugal. Next, a study about the current situation of these services in the country is presented, starting with an analysis of their organization, the type of actions/activities/services provided, as well as their accessibility. Results indicate that the Career Services in some Portuguese Higher Education Institutions appear not to be fully developed, and where they exist, they often focus mostly (and sometimes solely) upon job placement or internship provision. More investment is needed to meet the new employability needs and demands of both students (and their families) and the labor market.